Inversion of the Bessel potential operator in weighted variable Lebesgue spaces - Almeida, Alexandre (2008)
We study the inversion problem of the Bessel potential operator within the frameworks of the weighted Lebesgue spaces with variable exponent. The inverse operator is constructed by using pproximative inverse operators. This generalizes some classical results to the variable exponent setting. (c) 2007 Elsevier Inc. All rights reserved.